Exploring Mothers’ Experiences in Accessing Primary Healthcare Service Facilities in Rural Indonesia: Implication for Stunting Prevention - Ramadhaniyati; Lestari, Lilis; Saito, Ruka; Tsuda, Akiko (Al-Hijrah Indonesia, 2025)
Background: Primary healthcare service facilities are essential in preventing stunting by providing comprehensive support for mothers and children. The low usage of the primary health services by pregnant women and mothers with toddlers in rural Indonesia limits the effectiveness of the services and contributes to poor stunting prevention. Purpose: This study aimed to explore mothers' experiences in accessing healthcare services at primary healthcare facilities in Indonesia. Methods: This descriptive qualitative study was conducted in the Melawi district of West Kalimantan Province. Employing a purposive sampling technique, data were collected through in-depth interviews with six mothers, two pregnant and four mothers with children under two years. The data were analyzed through content analysis. Results: Most mothers in this study were high school graduates, of low economic status, aged 22 to 36 years, and from Dayak and Malay cultural backgrounds. Seven categories were identified: stigma in children with stunting, cultural and social norms influence, problems of knowledge and awareness, hierarchical communication between healthcare providers and mothers, trust issues with healthcare providers, equity and accessibility of healthcare service facilities, as well as limited information and education. Conclusions: Encouraging awareness campaigns is vital to address stunting stigmatization. Healthcare providers should improve communication, education strategy, and nutrition competency through targeted training to better support and rebuild trust with mothers. Healthcare institutions and policymakers should develop policies that improve health service quality. Strengthening advocacy roles and collaborating with community organizations could ensure equitable healthcare access.